A relação cuidador-bebê e os vínculos precários de uma sociedade líquida - SILVA, Luan Sampaio (Universidade Federal do Pará, 2025)
In contemporary times, we live in a time in which human relationships are increasingly fragile and inconsistent. Human beings, devoid of empathy, do not acquire the ability to genuinely care about the social and loving relationships they establish. This phenomenon is referred to by Bauman as “liquid modernity”. Despite describing the social phenomenon, it does not offer an answer, from a psychic point of view, about the reasons why people do not involve themselves emotionally in their relationships. The objective of this work is to analyze, in an interpretative way, the relationship between the caregiver and the baby and the fragility of human bonds from the perspective of the theory of personal maturation, developed by Winnicott. The psychoanalyst discusses the caregiver-baby relationship and the implications of this dyadic relationship in the formation of everyone’s personality by proposing his own knowledge called “Maturation Theory”, in which the baby’s developmental path in relation to his or her care environment is described. The propositions surrounding this theory will serve as the basis for the investigations and discussions in this thesis, in conjunction with studies by other psychoanalytic authors. Regarding the research methodology, it is composed of two stages: the first comprises the bibliographical review of some of the main classic works written by Bauman, Winnicott, among other psychoanalytic theorists, which addressed the construction and weaknesses of social bonds in the caregiverbaby interaction. In the second stage, the psychoanalytic-interpretive method will be adopted through the analysis of the film (directed by Lynne Ramsay) and fragments of the book (by Lionel Shriver) of the same name: “We need to talk about Kevin” (2011), with emphasis on the character Kevin and his environment/care network. The thesis is that liquid modernity and the fragility of social ties are a macrosocial phenomenon, composed of several microsocial phenomena that point to “environmental failures” in different spheres, but which, in a micro way, have their origins in the quality of the relationship between the caregiver-environment and the baby, in a specific primitive period of emotional development – the concern stage –, which compromises the achievement of the ability to care about others. We call this “net caregiver-baby relationship”.